Pengaruh penambahan bioetanol dari mahkota nanas terhadap emisi gas buang pada mesin motor 4 langkah - Aprilyanti, Selvia; Madagaskar, Madagaskar; Suryani, Faizah (TURBO [Tulisan Riset Berbasis Online], 2020)
Bioethanol is ethanol derived from plants that contain cellulose such as cassava, corn and sugar cane. The use of bioethanol aims to overcome the scarcity of fuel and reduce the use of fossil oil ingredients in Indonesia. The introduction of alternative energy is optimized by mixing fossil fuels with bioethanol. Therefore, the use of bioethanol as a renewable fuel is very good if because pure bioethanol has a high octane value of 118. Besides, bioethanol is also able to reduce the amount of carbon monoxide (CO) emissions, decrease Nitrogen Oxide (NOx) and hydrocarbon emissions compared to ordinary gasoline fuel. In this research, a mixture of Pertamax and Bioethanol with a mixture of variations, among others: pure Pertamax (E0), Pertamax mixture and bioethanol 5% (E5), bioethanol 10% (E10), and bioethanol 15% (E15). The fuel testing was carried out at the Environmental Service Laboratory using a 4-stroke Yamaha motorcycle brand. Mixing bioethanol as a fuel can reduce exhaust emissions from the combustion of motorcycle fuel 4 steps in all tests. The best test results obtained on the composition of the E10 fuel mixture with CO levels of 2.06%, CO2 levels of 6.96% and HC of 75 ppm.Keywords : Bioethanol, Gas Emissions, Hydrocarbons, Carbon Monoxide, Pertamax